Exploring Student Preferences for Online, Offline, and Hybrid Learning Systems in Higher Education - Fadhilah, Arisyah Dwi; Daulay, Rabiah Afifah; Selly, Rini; Pakpahan, Elyana Yulinda; Wardani, Tri Retno Kusuma (Aspirasi Masyarakat Intelektual Islam Nusantara, 2024)
In the context of higher education, the digital era and advancements in technology have revolutionized learning systems, necessitating an understanding of student preferences for online, offline, and hybrid methods. This study aims to investigate these preferences and the associated reasons behind them. Data were collected through a Google Form survey administered to 110 students of chemistry department, chemistry education study program, Universitas Negeri Medan, complemented by semi-structured interviews with a subset of participants. Results reveal that 9.1% of students prefer online learning due to its flexibility and cost-effectiveness, 55.5% favor offline (face-to-face) learning for its effectiveness in understanding material and fostering interaction, and 35.5% opt for a combination of both methods, which is perceived as the optimal balance. The findings underscore the importance of adapting learning methods to enhance educational effectiveness, addressing challenges such as internet access, device limitations, and transportation costs.